2000
DOI: 10.1353/anq.2000.0015
|View full text |Cite
|
Sign up to set email alerts
|

Girls with Guns: Narrating the Experience of War of Frelimo's "Female Detachment"

Abstract: This article examines the way in which female guerrillas both appropriated and contributed to the FRELIMO narrative of women's participation in the struggle for Mozambican liberation. The author argues that ideological commitment to the cause was essential to defining the experience of violence for these girls and young women and that, concurrent with their convictions, they felt empowered rather than victimized by the war. The article contributes to an emerging literature suggesting that the culturally-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…West (2000) identifies two major strands in this scholarship. The first is a Western psychological approach that asserts that exposure to violence leads to youths' loss of innocence; proponents argue that such young people go on to perpetuate violence throughout their lives, whether as victims of violence or its (often coerced) perpetrators (e.g., Boothby 1986).…”
Section: Youth and Violencementioning
confidence: 99%
See 1 more Smart Citation
“…West (2000) identifies two major strands in this scholarship. The first is a Western psychological approach that asserts that exposure to violence leads to youths' loss of innocence; proponents argue that such young people go on to perpetuate violence throughout their lives, whether as victims of violence or its (often coerced) perpetrators (e.g., Boothby 1986).…”
Section: Youth and Violencementioning
confidence: 99%
“…The first is a Western psychological approach that asserts that exposure to violence leads to youths' loss of innocence; proponents argue that such young people go on to perpetuate violence throughout their lives, whether as victims of violence or its (often coerced) perpetrators (e.g., Boothby 1986). The second approach centers on cultural agency and understands youth as able to adapt effectively to violent situations in culturally specific ways (Peters & Richards 1998, West 2000. Even when these two perspectives are combined, the romantic belief in a "lost generation" as the ultimate victims of war gives way to an analysis that recognizes both young people's agency in wartime and its very real constraints (Assal & Farrell 1992).…”
Section: Youth and Violencementioning
confidence: 99%
“…Arriving safely in Tanzania meant that many refugees necessarily re-established social relations. But under the auspices of FRELIMO and the Tanzanian authorities, they often found that their opportunities were usually limited as their gender roles and emotional vulnerability were shaped for the purposes of winning the anti-colonial war (West 2000;Sheldon 2002;Isaacman 1984;Machel 1969). Gender and age were especially important factors and played a determinant role in the refugee experience as young men were often conscripted into the military wing of FRELIMO.…”
Section: Benevolent Humanitarianism Meets Nascent Statecraftmentioning
confidence: 99%
“…123 One anthropological study that examined the experience of female fighters from Mozambique who participated in the FRELIMO independence movement is particularly useful because it was conducted two decades after women put down their arms. 124 Although a demobilization process occurred, it took no special consideration of female combatants and the difficulties that face them as they reintegrated into a patriarchal society after assuming traditionally "male" roles. During combat, when women began to frequently appear with guns slung over their shoulders, the elders of villages complained to guerilla leaders that this presented "an unacceptable challenge to 'traditional' societal relationships."…”
Section: Effects Of Transitional Justice On Colombian Female Combmentioning
confidence: 99%